STRATEGI PENGUATAN PENDIDIKAN AGAMA ISLAM MELALUI PERAN KELUARGA - Yuneta, Velly (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2025)
Islamic religious education plays a fundamental role in shaping an individual's character and morals from an early age. The family, as the first and foremost educational institution, holds a crucial key in instilling Islamic values. This research journal aims to identify effective strategies that families can implement to strengthen Islamic religious education within the home environment. This study employs a descriptive qualitative method with a literature review approach, collecting and analyzing secondary data from various scientific journals and credible books relevant to the topics of Islamic religious education in the family, the family's role in religious education, and strategies for its reinforcement. The research findings indicate that the active role of the family through exemplary behavior, habitual worship practices, instilling correct Islamic creed, teaching noble character, utilizing technology, and engaging in community religious activities are significant strategies in reinforcing the understanding and practice of Islam within the family. This study highlights the importance of parental awareness and commitment as primary educators in creating a religious and conducive family environment for the spiritual development of children. Furthermore, it emphasizes the implications for educators and policymakers in supporting efforts to strengthen Islamic religious education through the family